Украинский кризис в контексте стратегической ситиации на границе Армении и Арцаха с Азербайджаном - Гаспарян, Ангелина
The paper presents the Ukrainian crisis in the context of the strategic situation on the border of Armenia and Artsakh with Azerbaijan on the basis of a comparative analysis of the electronic media. Passing from one country to another, from one region to another in the search of the reasons, prerequisites and regulations, the traditional method of comparative analysis allows in the timeline to form the overall situation for getting the whole cause-and-effect pattern. Examination of the problem of standoff between the West and Russia in the light of the Ukrainian crisis provides a key to understanding the contemporary challenges and actions to ensure the safety of the two Armenian republics. В статье представлен украинский кризис в контексте стратегической ситуации на границе Армении и Арцаха с Азербайджаном на основе метода сравнительного анализа электрон¬ных СМИ. Традиционный сравнительный метод анализа в поисках причин, предпосылок и закономерностей позволяет, переходя от одной страны к другой, от одного региона к другому, сформировать общую ситуацию во временном отрезке для получения полной причинно-следственной картины. Рассмотрение проблемы противостояния Запада и России сквозь призму украинского кризиса дает ключ к пониманию современных вызовов и действию в обеспечении безопасности двух армянских республик.
Keywords: Հասարակական գիտություններ; Բնական գիտություններ